Antecedents of cyber security behavior: the roles of coping appraisal, threat appraisal and responsibility norms among government employees - Noor Suhani, Sulaiman (2023)
The value of cyber security awareness among employees plays an important role for organizations in the protection of assets. Cyber security has become a critical issue in society due to growing internet use. Various attitudes towards cyber security practices for employees in organizations are a major cause. Previous research has revealed that in the South East Asia region, Malaysia is reportedly the most vulnerable country, with 46% of respondents admitting to being victims of scams. Equally important, according to an Internet user survey in 2020 conducted by the Malaysian Communication and Multimedia Commission (MCMC), over the last six months, 53.1% of users have experienced cybercrime. On the other hand, 9.4% of users have experienced cybercrime in more than three years, 7.6% of users in the last two years and 27.7% of Internet users have experienced cybercrime in the previous 12 months in 2020. This study verify the extent of threat appraisal (perceived vulnerability, perceived severity), coping appraisal (perceived barrier, security response efficacy, response self-efficacy) and also to evaluate the impact level of responsibility norm (personal responsibility, third-party responsibility) on user‘s cyber security behaviour. Responsibility norms are integrated into the model as a means to assess employees‘ behaviors toward cybersecurity. This study also addresses a gap in the literature by investigating the extent to which the relationships between perceived vulnerability, perceived severity, perceived barrier, security response efficacy, response self-efficacy, personal responsibility, and third-party responsibility exist. A quantitative research design was used in this study. The designed model was tested in two stages of pre-test using structural equation modelling to analyze relationships between variables. 446 respondents from government agencies in Malaysia took part and were analysed using partial least-squares structural equation modelling (PLS-SEM). One of the most notable findings of this study is that cyber security behaviour has a significant impact on Malaysian government employees. These findings are one of the most critical findings from this study. The perceived severity, perceived barrier, response self-efficacy, personal responsibility, and third-party responsibility positively influenced cybersecurity behaviour. In contrast, the perceived vulnerability and security response efficacy have a negative impact on the government employee‘s cybersecurity behaviour in Malaysia. Thus, it concluded that the coping appraisal and responsibility norm associated with PMT has a significantly strong influence on the cyber security behaviour of Malaysian government employees than threat appraisal does. The outcomes of this study will demonstrate the actual findings that may be brought into effective action to decrease the impact of cyber-attacks on government employees in Malaysia. This study also has discovered the potential to contribute to the security of government agencies in Malaysia from cyber-attacks launched by perpetrators in cyberspace.